Penyuluhan Gemar Makan Ikan sebagai Upaya Peningkatan Pengetahuan Gizi Siswa Kelas VI di SDN 02 Dalam Kaum, Kecamatan Sambas - Harnatasya; Nadia; Putri Wulan; Deca Endy Rey; Nabila Naya Larasmita (CV. SINAR HOWUHOWU, 2025)
The fish consumption promotion counseling activity was conducted among sixth-grade students of SDN 02 Dalam Kaum, Sambas District, Sambas Regency, West Kalimantan Province. This activity aimed to improve students’ knowledge of fish, fish nutritional content, and processed fishery products, to build awareness of the importance of regular fish consumption as part of a healthy diet, and to encourage positive behavioral change by fostering interest and habits in choosing and consuming fish in daily life. The activity involved 47 students and was implemented through interactive lectures, discussions, and the use of visual and audio-visual media. The effectiveness of the activity was evaluated using pre-test and post-test assessments analyzed with the Normalized Gain (N-Gain) Score method. The results showed an increase in the average score from 78.9 in the pre-test to 91.3 in the post-test, with a mean improvement of 12.4 points. The average N-Gain value obtained was 0.68 or 68 percent, which falls into the moderately effective category. These findings indicate that the counseling activity successfully enhanced students’ understanding and awareness of the benefits of fish consumption and fostered positive attitudes toward fish as a nutritious food source. This activity is considered effective as a school-based nutrition education effort to support the development of fish consumption habits from an early age.